CLIMATE CHANGE AND WATER CRISIS IN AFGHANISTAN - Nabavi, Salman Ali; Mohammadi, Alinaqi (American International Journal of Social Science Research, 2024)
Though the negative impacts of climate change on water resources have become a severe social, economic, and environmental problem worldwide, especially in the arid regions of the earth, including Afghanistan, an inclusive and or conclusive review of diverse studies regarding the climate change and root causes of the water crisis in Afghanistan have not been carried out yet. This study analyses the negative impacts of climate change on water including the fundamental causes of the water crisis in Afghanistan, using analytical and descriptive approaches to review the related literature. The findings of this study show that although there is a strong relationship between climate change and water shortages, it can be a secondary factor in the case of Afghanistan. This is because the available surface water in Afghanistan is estimated to be about 50 percent higher than the country’s water needs. In addition, the main factors involved in Afghanistan’s water crisis are discussed in this study; factors that have not only caused the flow of about 67% of Afghanistan’s surface waters to neighboring countries but also caused the wastage of about 40% of its surface water during irrigation. In addition, limitations and recommendations for further studies are also presented. The result of this study would create a clear insight for researchers and policymakers to regulate and manage the ever-increasing water crisis conditions sustainably in Afghanistan and similar contexts. JEL Classification Codes: Q5, Q2, Q.